What Will Happen to This Dog? A Qualitative Analysis of Rehoming Organisations' Pre-adoption Dog Behaviour Screening Policies and Procedures - Griffin, Karen E.; John, Elizabeth; Pike, Tom; Mills, Daniel S. (Frontiers in Veterinary Science, 2022)
Rehoming organisations often undertake some type of temperament or behaviour evaluation to determine suitability of dogs for rehoming and/or the type of suitable home. Assessments can carry considerable weight in determining a dog’s fate. Although evaluation of the validity and reliability of any test is important, a more fundamental consideration is if the nature of the information sought and the weight given to this in the decision making of organisations is of more than anecdotal value. Therefore, this study’s aim was to conduct a qualitative analysis of rehoming organisations’ pre-adoption dog screening practices and potential justifications, comparing this with the available scientific evidence. A written enquiry was sent to rehoming organisations in the UK and the US. Of 73 respondents, the majority conducted assessments for all dogs pre-adoption. Using a thematic analysis, nine themes and 71 sub-themes emerged concerning the types of information respondents aim to gather from assessments. The majority of respondents used, at least partially, pass/fail scoring, i.e. certain outcomes would lead to dogs being deemed unadoptable. Forty-one sub-themes and one theme were identified as potentially leading to a dog being deemed unadoptable. The evidence base for these factors was identified from the scientific literature relating to: increased risk for relinquishment, impact on a dog’s quality of life, and human safety risk. Evidence supported ten factors: “aggression toward people”, “aggression toward cats or other animals”, “aggression towards dogs”, “biting or snapping”, “resource guarding”, “activity level or exercise needs”, “destructiveness”, “housetrained”, “fearfulness”, and “knowledge of basic commands and/or general training”. Of those, seven were associated only with relinquishment risk, two (“resource guarding” and “knowledge of basic commands”) with human safety risk, and one (“fearfulness”) with both. Five had been described in the current study as characteristics that would lead to a dog being unadoptable. Thus, for >85% of characteristics organisations deemed important for a dog’s adoptability, scientific evidence to support this is lacking. Given the lack of scientific support for many decisions regarding dogs’ rehoming suitability and recognised pressure on resources, it is suggested that organisations should consider focusing on post-adoption care to ensure placement success.